(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Different non-motor neurological complaints are reported among the Parkinson’s disease patients. Objective: The purpose of the present study was to see the non-motor neurological complaints of Parkinson’s disease patients. Methodology: This cross-sectional study was carried out in the in-patient and out-patient Department of Medicine and Neurology of Sir Salimullah Medical College and Mitford Hospital, Dhaka from July 2012 to December 2013 for a period of one and half year. All patients with Parkinson’s disease who were admitted under department of Medicine and Neurology and also who visited out-patient department of Medicine and Neurology of Sir Salimullah Medical College and Mitford Hospital, Dhaka were included as study population. Patients who were diagnosed according to Brain Bank clinical criteria for diagnosis of Parkinson’s disease were included in this study. The non-motor neurological complaints were recorded. Result: This study was conducted in Sir Salimullah Medical College and Mitford Hospital with a view to see the non-motor neurological complaints of Parkinson’s disease. The mean age was found 69.15±10.08 years. Most of the patients had a combination of non-motor symptoms and among them more than two third (66.7%) of the patients had cognitive impairment; furthermore more than half (53.8%) of the patients had sleep disturbance. One fourth (25.0%) of patients had sensory, sleep and cognitive disorder; however, 9(22.5%) patients had sleep and cognitive disorder. Conclusion: In conclusion majority Parkinson’s disease patients are suffering from cognitive impairment followed by sleep disturbances. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 123-126